Proposed Marketing Strategy For Hijab2day - Rahma Putri, Aldila; Fachira, Ira (Universitas Negeri Surabaya, 2020)
The economic growth of Muslim middle class society in Indonesia has started a hijab revolution among the Muslim women and this fashion trend provides new opportunities for fashion businesses to focus on to Islamic fashion, especially hijab. The prospect of hijab business is promising, especially with the advancement of communication technology, making the process of trading online much simpler for both sellers and buyers. Hijab2day is one hijab businesses who uses Instagram as their trading platform and in the last five years, they have been offering a variety of hijab designs and hijab accessories online. However competition is unavoidable and the simplicity of trading online has attracted new people to venture into the hijab business. Hijab2day admits that competitors with stronger promotion and marketing strategy have become a particular concern, and with a decrease in sales in 2015, Hijab2day feels that this is something that needs to be analyzed further. This research is designed to highlight Hijab2day’s problems that affected their performance in 2015 as well as to propose a better marketing strategy that will increase Hijab2day’s sales. To identify Hijab2day’s problems, this research conducted PESTEL analysis, Competitor analysis and Porter 5 Forces analysis. Researcher also conducted marketing analysis using Marketing Mix analysis and STP analysis. A SWOT analysis was also conducted to identify Hijab2day’s strengths and weaknesses, which will help to form a more efficient strategy to develop the business. This research analyzed 164 questionnaires, filled by respondents who are all Muslim women who are often purchase hijabs online. The respondents come from different ages and backgrounds. Based on the questionnaire, researcher found out that most respondents are more responsive to a ‘buy 2 get 1’ promotional method, the second highest of the questionnaire result are more receptive towards hijab related promotional event, while 16 respondents suggest holding ‘sales’ would be more attractive. Nearly all respondents prefer to shop via Instagram, while half of the respondents choose to browse and purchase through company’s websites. Research also found out that half of the respondents tend to go online between 18.00 and 21.00. Based on these findings, researcher is recommending three new strategies to improve Hijab2day’s promotional and marketing approach, which will hopefully lead to sales growth : to create better promotional and marketing approach, utilize the new insights of the importance of timing in social media by scheduling posts at the most efficient time for maximum exposure, improve and expand Hijab2day sales platform, expand Hijab2day chosen communication platforms. Researcher hopes that by implementing the recommended suggestions, Hijab2day can maximize their sales and increase growth.